2007
DOI: 10.1038/nbt1354
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of the myxobacterium Sorangium cellulosum

Abstract: The genus Sorangium synthesizes approximately half of the secondary metabolites isolated from myxobacteria, including the anti-cancer metabolite epothilone. We report the complete genome sequence of the model Sorangium strain S. cellulosum So ce56, which produces several natural products and has morphological and physiological properties typical of the genus. The circular genome, comprising 13,033,779 base pairs, is the largest bacterial genome sequenced to date. No global synteny with the genome of Myxococcus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
243
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(255 citation statements)
references
References 48 publications
9
243
1
2
Order By: Relevance
“…The genome of S. cellulosum (account no. AM746676; Schneiker et al, 2007) contains two complete rRNA operons (16S-23S-5S), one incomplete (16S-23S) and one with two 5S rRNA genes (16S-23S-5S-5S).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genome of S. cellulosum (account no. AM746676; Schneiker et al, 2007) contains two complete rRNA operons (16S-23S-5S), one incomplete (16S-23S) and one with two 5S rRNA genes (16S-23S-5S-5S).…”
Section: Discussionmentioning
confidence: 99%
“…In this complex, densitydependent life style, signalling compounds have a key role (Goldman et al, 2006), and myxobacteria are well known for the production of various secondary metabolites and thus are prime targets for the search of new secondary metabolites (Gerth et al, 2003;Wenzel and Mü ller, 2007;Weissman and Mü ller, 2010). They contain the largest genomes of all prokaryotes and the genome of Sorangium cellulosum, with 413 Mbp as the largest bacterial genome sequenced to date (Schneiker et al, 2007). Myxobacteria form a phylogenetically coherent group and constitute the order Myxococcales in the class Deltaproteobacteria.…”
Section: Introductionmentioning
confidence: 99%
“…It has, however, been speculated that species living in invariant niches tend to have small genomes, as stability acts to reduce genome size due the metabolic burden of replicating DNA with no adaptive value (Giovannoni et al, 2005(Giovannoni et al, , 2014 such as in obligatory and intracellular pathogens or mutualists (Moran, 2003;Klasson and Andersson, 2004;Moya et al, 2009). Due to their metabolic diversity, species with large genomes are potentially able to tackle a wider range of environmental conditions (Schneiker et al, 2007) and tend to be more ecologically successful where resources are scarce but diverse, and where there is little penalty for slow growth (Konstantinidis and Tiedje, 2004). The effect by which these two opposing evolutionary forces exert on the overall distribution of genome sizes was first observed by Koonin and Wolf in 2008, where it was reported that bacterial genome sizes show a bimodal distribution (Koonin and Wolf, 2008).…”
mentioning
confidence: 96%
“…This appears to be a common feature for the genus Amycolatopsis, because this circular topology was also suggested for the Amycolatopsis orientalis chromosome [14]. With a total length of 10 236 715 base pairs (bps) ( Table 1, GenBank accession number CP002000), the A. mediterranei genome is larger than that of S. coelicolor and S. erythraea, but smaller than that of the myxobacterium Sorangium cellulosum [15], and is apparently one of the largest prokaryotic genomes sequenced so far. The outer scale is numbered in megabases and indicates the core (red), quasi-core (orange), and non-core (sky blue).…”
Section: General Features Of a Mediterranei Genomementioning
confidence: 99%